Direct experimental evidences of the density variation of ultrathin polymer films with thickness. (16th July 2021) - Giermanska, Joanna; Ben Jabrallah, Soumaya; Delorme, Nicolas; Vignaud, Guillaume; Chapel, Jean-Paul
Abstract: Beyond the peculiar glass transition temperature (Tg) studied extensively for over two decades, we have investigated in this work the variation of the mass density of polymer thin films, a key property barely put forward in the literature. We were able to directly measure the mass density of polystyrene (PS) and poly (methyl methacrylate) (PMMA) thin films as a function of their thickness from accurate Quartz Crystal Microbalance (QCM) dissolution experiments. Depending on the chemical nature of the polymers, the results showed an unambiguous variation of the mass density when the film thickness was reduced: an increase for PS and a decrease for PMMA films. In the last part, we measured the coefficient of thermal expansion (CTE) of both polymers to rationalize the apparent inconsistency of an increase/decrease in the mass density with the commonly observed depression/rise of the Tg of PS/PMMA films. Surprisingly, the coefficient of thermal expansion and the mass density showed a similar variation with thickness, pointing out a clear correlation between the glass transition temperature, the coefficient of thermal expansion and the free volume of the polymer. Graphical abstract: Image 1 Highlights: The density of polymer films can be measured using QCM dissolution experiments without the need of any model. The density of PS and PMMA thin films (<100 nm) does vary in the opposite way with thickness. The density and the coefficient of thermal expansion (CTE) of PS and PMMA films show a similar behavior with thickness. There exists a possible correlation between Tg, CTE and the free volume of polymer thin films.